Modulation of inwardly rectifying K+ channel by intracellular and extracellular pH in bovine aortic endothelial cells - Park, K.-S.; Kong, I.D.; Lee, J.W.; Rhim, H.; Kim, Y.C.; Seo, In Seok; Kim, K.W. (2002)
The effects of intracellular and extracellular pH on the inwardly rectifying K+ (IRK) channel of the bovine aortic endothelial cells (BAECs) were examined using whole-cell patch-clamp technique. The IRK current, efficiently blocked by Ba2+ (200 μM), is the most prominent membrane current in BAECs, which mainly determines the resting membrane potential. The expression of Kir2.1 was observed in BAECs using reverse transcriptase-polymerase chain reaction (RT-PCR) analysis. Intracellular alkalinization, elicited by the extracellular substitution of NaCl with NH4Cl (30 mM), significantly augmented the amplitude of IRK current. On the contrary, the amplitude of IRK current was attenuated by the Na-acetate (30 mM)-induced intracellular acidification. The changes in extracellular pH also closely modulated the amplitude of IRK current, which was decreased to 40.2±1.3% of control upon switching the extracellular pH to 4.0 from 7.4. The extracellular pH value for half-maximal inhibition (pK) of IRK current was 5.11. These results demonstrate that the activity of IRK channel in BAECs, probably Kir2.1, was suppressed by proton at both sides of plasma membrane.
Keywords: acetic acid; ammonium chloride; barium; inwardly rectifying potassium channel; potassium ion; proton; sodium chloride; acidification; action potential; alkalinization; amplitude modulation; animal cell; aorta; artery endothelium; article; attenuation; cattle; cell membrane; cell pH; controlled study; endothelium cell; inhibition kinetics; membrane current; membrane steady potential; nonhuman; patch clamp; potassium current; protein expression; reverse transcription polymerase chain reaction